Efficacy and safety of triple therapy with dapagliflozin add‐on to saxagliptin plus metformin over 52 weeks in patients with type 2 diabetes. Issue 11 (19th August 2016) - Mathieu, C.; Herrera Marmolejo, M.; González González, J. G.; Hansen, L.; Chen, H.; Johnsson, E.; Garcia‐Sanchez, R.; Iqbal, N.
Abstract : We previously reported that dapagliflozin versus placebo as add‐on to saxagliptin plus metformin resulted in greater reductions in glycated haemoglobin (A1C), fasting plasma glucose (FPG) and body weight (BW) after 24 weeks of treatment in patients with type 2 diabetes (T2D). Here we report results after 52 weeks of treatment. Patients stabilized on open‐label metformin and saxagliptin 5 mg/day for 8‐16 weeks were randomized to placebo or dapagliflozin 10 mg/day plus open‐label saxagliptin plus metformin for 52 weeks. Changes from baseline to week 52 were greater with dapagliflozin versus placebo in A1C (−0.74% vs. 0.07%), FPG (−27 vs. 10 mg/dL) and BW (−2.1 vs. −0.4 kg). More patients achieved A1C <7% with dapagliflozin (29.4%) versus placebo (12.6%). Adverse events were similar with dapagliflozin (66%) and placebo (71%), and hypoglycaemia was rare (≤2%). Genital infections occurred more often with dapagliflozin (6%) than with placebo (1%); frequency of urinary tract infections was similar between the two groups (9% vs. 10%). Triple therapy with dapagliflozin add‐on to saxagliptin plus metformin is a durable, effective and well‐tolerated intervention for the treatment of T2D.